Migración y trabajo en la era de la globalización: el caso de la migración México-Estados Unidos en la década de 1990 - Canales, Alejandro I. (Papeles de Población, 2021)
Mexican migration into the United States started at the end of the XIX century. This social phenomenon has presented multiple stages and has occurred in different economic and political circumstances. This paper will document the new modalities and patterns present in the actual historic, economic and social context of migration in the era of “globalization”. Special attention is paid to the new modalities of migration and the people incorporating into the migration flow, as well as, the structural conditions of migration in Mexico and the instability and vulnerability of the United States labor market.